Development of somatic cell nuclear transfer biotechnology for cloning of animals: a mini-review - Rosyid Ridlo Al Hakim; Tegar Aldi Saputro (Universitas Ahmad Dahlan, 2021)
Somatic cell nuclear transfer (SCNT) in cloning animals is important for reproductive biotechnology, it can be used for the conservation of wild, endangered or critically endangered, and also to improve superior local livestock genetic resources. So many publications that show the success of animal cloning with SCNT for various purposes, as well as the development of animal cloning methods. This paper will attempt to review the results of successful and limited animal cloning research on the needs of non-threatened (livestock and wild animals) and threatened wildlife. This research was kind of literature review. The research was conduct several phase these are identification, abstract screening, full-text selection, and mini-review writing. The results of SCNT biotechnology for animal cloning can be used for the preservation of wild animal germplasm genetic resources, increasing the production of superior livestock and ways of conserving threatened animals.